LSM INTERNASIONAL DAN DILEMA PELESTARIAN DI HUTAN HARAPAN PROVINSI JAMBI - Adirini Pujayanti (Sekretariat Jenderal DPR RI, 2014)
This paper discusses the environmental conservation efforts by international NGOs in Indonesia. Through a global partnership mandated by the Earth Summit in 1992, all parties are expected to involve a full role to playas well as topreserve the environment. Deforestation in thetropical forests in Sumatra has attracted global great attention. This condition has encouraged international NGOs to carry out conservation in the area of the Hope Forest in the Province of Jambi which has a fairly high level of biodiversity. However, this effort has gainned pros and cons.